Pengaruh Permainan Kosakata Bahasa Inggris Melalui Digital Smart Board For Kids Terhadap Perkembangan Bahasa Anak Usia 5-6 Tahun di Era Merdeka Belajar - Kristin Anggraini; Maria Josephine Kriesye S.; Ruruh Mindari (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2022)
This research will use the Digital Smart Board for Kids game as a means of learning English vocabulary for young children. This study uses a type of quantitative research using a pre-experimental design with one group pretest-posttest. The research subjects in this study were 15 children aged 5-6 years. The selection of subjects takes into account the application of foreign languages, especially English in teaching and learning activities in kindergarten. Data collection techniques using observation and documentation. To draw conclusions from the research results, a hypothesis test was carried out using the t-test. Before conducting the t-test, the normality test and homogeneity test were first carried out on the research results. Where the alpha value is more than 0.05, the data is considered good and reliable. Hypothesis testing was carried out to determine the effect of English vocabulary games through the Digital Smart Board for Kids on the language development of children aged 5-6 years in the independent learning era. This Digital Smart Board game for kids can be played by all children, so that development in the classroom becomes more applicable, contextual and interesting. In conclusion, the Digital Smart Board game for kids can be used to develop children's language development properly, especially in terms of understanding, remembering and pronouncing/imitating English vocabulary in children aged 5-6 years in the era of independent learning.